Material didáctico para el desarrollo de la comprensión de lectura con adultos mayores - Marina Sorza Urrego, Maria Flor (Universidad Antonio Nariño, 2023)
The degree work was designed thinking about strategies that encourage reading comprehension in the elderly. This idea was born with the case of Amparo Arcila who came to the Talentos school with the desire to study at the age of 72, seeking to achieve goals that she did not achieve when she was young. The didactic material was designed with the aim of strengthening reading comprehension skills. This didactic material contains two booklets: the teacher's guide and the activity booklet for students